2006
DOI: 10.1097/00007691-200608000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring for Dose Individualization of Cisplatin in Testicular Cancer Patients Based Upon Total Platinum Measurement in Plasma

Abstract: Cisplatin (CDDP) is an anticancer agent widely used in testicular cancer, for which pharmacokinetic (PK)/pharmacodynamic relationships have usually been based upon measurement of its unbound fraction in plasma. Because it has been shown that free CDDP clearance can be related to patient's body surface area (BSA), dosage is mostly adjusted a priori using only this single parameter, with mixed results for accurately predicting CDDP exposure and reducing toxicities. In contrast, the authors present here an origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Several studies have demonstrated that the response to HD-MTX is correlated with the delivered dose and the serum level of MTX, thus stressing the need for developing adaptivedosing methods [3,4,6,21]. Our institute has developed over the past decade Bayesian, dynamic adaptive dosing with feedback methods, which can be applied to various anticancer drugs such as CDDP, CBDCA, etoposide and MTX [11,[22][23][24]. Dose adjustment is normally performed, to reach a predetermined plasma concentration that is associated with optimal response and fully manageable toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the response to HD-MTX is correlated with the delivered dose and the serum level of MTX, thus stressing the need for developing adaptivedosing methods [3,4,6,21]. Our institute has developed over the past decade Bayesian, dynamic adaptive dosing with feedback methods, which can be applied to various anticancer drugs such as CDDP, CBDCA, etoposide and MTX [11,[22][23][24]. Dose adjustment is normally performed, to reach a predetermined plasma concentration that is associated with optimal response and fully manageable toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…In testicular cancer cases, plasma levels of cisplatin equivalent to a C max of 1.95 μg/ml are typical targets. 34 In addition to causing aberrant cross-linking of…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…This indicates that total Pt may be used as a marker for the active amount, as has been done in recent clinical pharmacokinetic studies (Salas et al, 2006). Furthermore, analysis of total Pt is technically easier to perform, especially with the small perilymph samples we obtained.…”
Section: Discussionmentioning
confidence: 56%